Intra-Regional Spillovers in South America : Is Brazil Systemic After All? - Sosa, Sebastian (IMF Working Papers; Working Paper ;, 2012)
Shocks stemming from Brazil - the large neighbor in South America - have historically been a source of concern for policy-makers in other countries of the region. This paper studies the importance of Brazil's influence on its neighboring economies, documenting trade linkages over the last two decades and quantifying spillover effects in a Vector Auto Regression setting. While trade linkages with Brazil are significant for the Southern Cone countries (Argentina, Bolivia, Chile, Paraguay, and Uruguay), they are very weak for others. Consistent with this evidence, econometric results show that, while the Southern Cone economies (especially Mercosur's members) are vulnerable to output shocks from Brazil, the rest of South America is not. Spillovers can take two different forms: the transmission of Brazil-specific shocks and the amplification of global shocks-through their impact on Brazil's output. Finally, we also find suggestive evidence that depreciations of Brazil's currency may not have significant impact on output of its key trading partners.